The Principle of Freedom of Contract in Commercial Agreements: Are Limitations Needed? - Agustini, Shenti; Jaya, Febri; Agustianto, Agustianto (Universitas Medan Area, 2023)
The principle of freedom of contract is one of the principles in an agreement where the parties can determine for themselves the form of the agreement that will be made. However, by implication, this principle reaps many injustices. One form of implementation of this principle is standard agreements made in the business world. Standard agreements are only made unilaterally so they have the potential to cause injustice. This research aims to analyze whether or not restrictions are necessary in the principle of freedom of contract. The research method used is normative juridical. The theoretical basis used is Economic Democracy Theory. The research results show that the principle of freedom of contract has resulted in a lot of injustice, for example, standard agreements are made in the business world for time efficiency but do not involve the parties in making them, so there are parties whose position is very weak in the agreement. This is not by the theory of economic democracy which should provide prosperity for all, not just certain parties. Therefore, it is necessary to limit the principle of freedom of contract.